Biofilm formation, adherence, and hydrophobicity of M. sympodialis, M. globosa, and M. slooffiae from clinical isolates and normal skinVirulence factors of M. sympodialis, M. globosa and M. slooffiae - Angiolella, Letizia; Rojas, Florencia; Mussin, Javier; Greco, Rosa; Sosa, María de Los Angeles; Zalazar, Laura; Giusiano, Gustavo (Medical mycology (Oxford), 2020)
The genus Malassezia comprises a heterogeneous group of species that cause similar pathologies. Malassezia yeasts were considered as the most abundant skin eukaryotes of the total skin mycobiome. The ability of this fungus to colonize or infect is determined by complex interactions between the fungal cell and its virulence factors. This study aims to evaluate in vitro the hydrophobicity levels, the adherence capacity on a polystyrene surface and the ability to form biofilm of 19 isolates, including M. sympodialis, M. globosa, and M. slooffiae, from healthy subjects and from dermatological disorders. Cellular surface hydrophobicity levels were determined by two-phase system. The biofilm formation was determined by tetrazolium salt (XTT) reduction assay and by Scanning Electron Microscopy (SEM). Strain dependence was observed in all virulence factors studied. All isolates of M. sympodialis, M. globosa, and M. slooffiae demonstrated their ability to form biofilm at variable capacities. SEM observations confirmed a variable extracellular matrix after 48 hours of biofilm formation. All isolates of M. globosa were highly adherent and/or hydrophobic as well as biofilm producers. In contrast, M. slooffiae was the least biofilm producer. No significant differences between virulence factors were demonstrated for M. sympodialis, either as clinical isolate or as inhabitant of human microbiota. Results of this work together with the previous M. furfur research confirm that the most frequently Malassezia species isolated from normal subject's skin and patients with dermatosis, form biofilm with different capacities. The study of these virulence factors is important to highlight differences between Malassezia species and to determine their involvement in pathological processes.